1998
DOI: 10.1021/la970761o
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermolecular and Interfacial Interactions on the Three- and Two-Dimensional Structure and Phase Behavior of Three-Block Liquid-Crystalline Siloxane Derivatives

Abstract: Using several experimental techniques, we have investigated the thermodynamics and the structure of the bulk, monolayers, and multilayers of new three-block organosiloxanes based on the pentyloxy-4′-cyanobiphenyl mesogenic unit. Compared to conventional amphiphiles or smectogens, these molecules contain an additional siloxane moiety whose bulkiness was gradually increased. This enables fine tuning of the steric effect imposed by the siloxane parts and allows determination of the balance between moleculesubstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
4
22
0
Order By: Relevance
“…The reversible formation of well defined single, triple, and even thicker multilayers by compression of monolayers was also reported for amphiphilic liquid crystals with a polar group at only one end, and incorporated rodlike105–110 or disclike anisometric units 111. For these compounds, a predominately vertical or tilted alignment of the rigid cores was observed, whereas bolaamphiphiles with polar groups at both ends adopt the side‐on arrangement in monolayers 112.…”
Section: Self‐assembly Of T‐shaped and X‐shaped Polyphiles At Intesupporting
confidence: 54%
See 1 more Smart Citation
“…The reversible formation of well defined single, triple, and even thicker multilayers by compression of monolayers was also reported for amphiphilic liquid crystals with a polar group at only one end, and incorporated rodlike105–110 or disclike anisometric units 111. For these compounds, a predominately vertical or tilted alignment of the rigid cores was observed, whereas bolaamphiphiles with polar groups at both ends adopt the side‐on arrangement in monolayers 112.…”
Section: Self‐assembly Of T‐shaped and X‐shaped Polyphiles At Intesupporting
confidence: 54%
“…This indicates that the proper combination of rigid rodlike and flexible units is a general approach to fluid, but well defined mono‐ and multilayers. Moreover, depending on the molecular topology, either SmA or SmC‐like structures (aromatic cores perpendicular or tilted to the layer planes)105–108 or structures similar to the Lam phase,28 where the aromatic cores are aligned parallel to the layers, could be obtained. The former type is typical for linear rodlike amphiphiles without lateral chains, whereas the latter has become available with the T‐shaped and X‐shaped polyphiles 103…”
Section: Self‐assembly Of T‐shaped and X‐shaped Polyphiles At Intementioning
confidence: 99%
“…The bulge amphiphile Langmuir film is treated in terms of sublayers, as suggested by Ibn-Elhaj et al [21]. The main rise in surface pressure coincides with the bulge group sublayer reaching a closely packed arrangement near 38 Å 2 /molecule.…”
Section: Bulge Amphiphile Reversible Collapse Mechanismmentioning
confidence: 99%
“…Ibn-Elhaj et al have observed a small entropy increase for the monolayerto-multilayer transition for films derived from three-block organosilane amphiphiles 5AB 2 and 5AB 3 . They ascribe the small entropy increase to a change in water ordering [21]. Plehnert et al have examined a series of mesogenic amphiphiles in which the liquid crystalline and Langmuir film ordering are in competition.…”
Section: Entropy Of the Reversible Collapse Transitionmentioning
confidence: 99%
See 1 more Smart Citation